The Immunisation Dilemma—Part 5: Towards International Agreement on Homoeoprophylaxis - Golden, Isaac (Homœopathic Links, 2015)
Responses collected during two international surveys of homeopathic practitioners' attitudes towards and use of homoeoprophylaxis (HP), together with evidence presented in the first four parts of the series, have resulted in a statement of what is known about HP as well as a statement of a majority position regarding HP. One unambiguous finding is that education in HP is inadequate. Also, confidence in the evidence base of HP is strong but not sufficient. More research is needed. Though it is clear that complete consensus is not possible, this majority position has the potential to lead to improved education in HP, more focused research and a more coordinated approach to HP by practitioner associations internationally.
Keywords: Homoeoprophylaxis; Immunisation; Vaccination; International consensus; Majority position